STRIVING TOWARDS HUMANISING EXCELLENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – The School of Management (PPP) Universiti Sains Malaysia (USM) is striving to produce excellent talents with humanistic values (‘insan’) to ensure a more sustainable future.